Sarcopenia in patients after an episode of acute decompensated heart failure: An underdiagnosed problem with serious impact. Issue 6 (June 2021) - Eschalier, Romain; Massoullié, Grégoire; Boirie, Yves; Blanquet, Marie; Mulliez, Aurélien; Tartière, Pierre-Louis; Anker, Stefan; D'Agrosa Boiteux, Marie-Claire; Richard, Ruddy; Jean, Frédéric; Combaret, Nicolas; Souteyrand, Géraud; et al.
Summary: Background & aims: Sarcopenia is a multifactorial syndrome resulting in a decrease in both muscle mass and function. Little is known about the prevalence and prognostic impact of sarcopenia in patients with acutely decompensated chronic heart failure (ADHF). We aimed to evaluate the prevalence (main endpoint) and impact of sarcopenia on ADHF patients. Methods: 140 ADHF patients were enrolled between November 2014 and September 2018 in a multicenter prospective longitudinal study. A similar, independent multi-departmental cross-sectional study in 165 ADHF patients was used for external validation of prevalence data. All subjects were assessed on the European Working Group on Sarcopenia criteria. Results: Ninety-one patients (65%) had sarcopenia (vs. 53.6% in the external replication regional cohort). Patients with sarcopenia were older and more likely to have eGFR <60 ml/min/1.73 m 2 (p < 0.001 and p = 0.002). Sarcopenia was associated with impaired functional status [lower 6 min walking test (220 ± 108 vs. 279 ± 170, p = 0.03) and 4 m gait speed (0.56 ± 0.24 vs. 0.80 ± 0.37, p < 0.001)] and autonomy [Instrumental activities of daily living: 6.7 ± 1.4 vs. 7.3 ± 1.2, p = 0.005]. Over up to 4 years' follow-up, 30 cardiovascular (CV) deaths and 42 non-CV deaths occurred. In a multivariable analysis, sarcopenia was associated with time to first non-CV hospitalization (hazard ratio 1.93; 95% confidence interval 1.14–3.24; p = 0.014) but not with any other hospitalization, any mortality endpoint, or a composite endpoint of CV death and HF hospitalization. Conclusions: The prevalence of sarcopenia in ADHF patients is high and associated with greater risk of non-CV hospitalizations, highlighting the importance of identifying and managing the condition in a multidisciplinary approach. Clinical trial registration: NCT03153774. Highlights: First study in such population. High prevalence of sarcopenia and higher risk for non-CV hospitalizations. Clinicians need to improve diagnosis of sarcopenia and test new strategies.